Post a New Question

math

posted by .

Given that x = 2log t is a solution of the equation10^(2x+1) -7(10^x) -26 =0. Find t

  • math -

    10^(2x+1) -7(10^x) -26 = 0
    10*10^2x - 7*10^x - 26 = 0
    10*10^(2*2log t) - 7*10^(2log t) - 26 = 0
    10*10^(4log t) - 7*10^(2log t) - 26 = 0
    10*(10^(log t))^4 - 7*(10^(log t))^2 - 26 = 0
    10t^4 - 7t^2 - 26 = 0
    (10t^2+13))(t^2-2) = 0
    t = ±√2 or ±√(13/10) i

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question